2015
DOI: 10.1890/es15-00342.1
|View full text |Cite
|
Sign up to set email alerts
|

Functional identity explains carbon sequestration in a 77‐year‐old experimental tropical plantation

Abstract: Planting forests is an important practice for climate change mitigation, especially in the tropics where the carbon (C) sequestration potential is high. Successful implementation of this mitigation practice requires knowledge of the role of species identity and diversity on carbon accrual of plantations. Despite this need, solid data on the long-term development of forest plantations are still very scarce. Monospecific and two species mixture plots of a 77-year-old tree diversity experiment in Yangambi in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
(38 reference statements)
3
11
0
Order By: Relevance
“…This demonstrates that tropical tree species, when grown alone, do display the large range of variation in the ecosystem properties we evidenced in our simulations (see also Bauters et al. ).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…This demonstrates that tropical tree species, when grown alone, do display the large range of variation in the ecosystem properties we evidenced in our simulations (see also Bauters et al. ).…”
Section: Discussionsupporting
confidence: 72%
“…In our simulations, the major impact of species diversity on GPP was the selection effect, the influence of a selective group of efficient species on the ecosystem, rather than a complementarity effect in resource acquisition across species niches. This finding contrasts with some empirical studies where a stronger complementarity than selection effect was evidenced (Loreau and Hector 2001), but is in agreement with empirical results in tropical forests (Bauters et al 2015, Finegan et al 2015, Chiang et al 2016, Prado-Junior et al 2016. However, our model does not include any other resource limitation than light, especially nutrient and water limitations.…”
Section: Biodiversity and Ecosystem Functioningsupporting
confidence: 79%
See 2 more Smart Citations
“…Previous biodiversity–ecosystem functioning studies yielded contrasting results on the relative importance of the different biodiversity effects in tropical forests. While the complementarity effect was identified as the dominant effect in some studies (Huang et al, ; Niklaus et al, ), the selection effect was identified in others (Bauters et al, ; de Avila et al, ; Finegan et al, ; Lohbeck, Bongers, Martinez‐Ramos, & Poorter, ; Maréchaux & Chave, ; Tobner et al, ). Our results suggest that the mechanisms through which biodiversity influences forest functioning depend to a great extent on the state of the ecosystem and its history of disturbances, with a complementarity effect dominating in recently (i.e.…”
Section: Discussionmentioning
confidence: 99%